Effects of ethanol on aggregation, serotonin release, and amyloid precursor protein processing in rat and human platelets. (February 2014) - Ehrlich, Daniela; Humpel, Christian
<x xml:space="preserve">Abstract</x> It is known that oxidative stress leads to amyloid precursor protein (APP) dysregulation in platelets. Ethanol (EtOH) is a vascular risk factor and induces oxidative stress. The aim of the present study was thus to investigate whether EtOH affects APP processing in rat and human platelets. Platelets were exposed to 50 mM EtOH with and without 2 mM calcium-chloride (CaCl2) for 20 or 180 minutes at 37°C. Platelet aggregation, serotonin release and APP isoforms 130 and 106/110 kDa were analyzed. As a control, 100 mM H2O2 was tested in rat platelets. Our data show that EtOH alone did not affect any of the analyzed parameters, whereas CaCl2 significantly increased aggregation of rat and human platelets. In addition, CaCl2 alone enhanced serotonin release in rat platelets. EtOH counteracted CaCl2-induced aggregation and serotonin release. In the presence of CaCl2, EtOH reduced the 130 kDa APP isoform in rat and human platelets. In conclusion, this study shows that in the presence of CaCl2, EtOH affects the platelet function and APP processing in rat and human platelets.